Did I find the right examples for you? yes no

All Samples(10)  |  Call(8)  |  Derive(0)  |  Import(2)

src/s/y/sympy-HEAD/sympy/integrals/tests/test_transforms.py   sympy(Download)
from sympy.integrals.transforms import (mellin_transform,
    inverse_mellin_transform, laplace_transform, inverse_laplace_transform,
    fourier_transform, inverse_fourier_transform,
    sine_transform, inverse_sine_transform,
    cosine_transform, inverse_cosine_transform,
    a = symbols("a")
 
    assert hankel_transform(1/r, r, k, 0) == 1/k
    assert inverse_hankel_transform(1/k, k, r, 0) == 1/r
 
    assert hankel_transform(
        1/r**m, r, k, 0) == 2**(-m + 1)*k**(m - 2)*gamma(-m/2 + 1)/gamma(m/2)
        2**(-m + 1)*k**(m - 2)*gamma(-m/2 + 1)/gamma(m/2), k, r, 0) == r**(-m)
 
    assert hankel_transform(1/r**m, r, k, nu) == (
        2*2**(-m)*k**(m - 2)*gamma(-m/2 + nu/2 + 1)/gamma(m/2 + nu/2))
    assert inverse_hankel_transform(2**(-m + 1)*k**(
        m - 2)*gamma(-m/2 + nu/2 + 1)/gamma(m/2 + nu/2), k, r, nu) == r**(-m)
 
    assert hankel_transform(r**nu*exp(-a*r), r, k, nu) == \

src/s/y/sympy-0.7.5/sympy/integrals/tests/test_transforms.py   sympy(Download)
from sympy.integrals.transforms import (mellin_transform,
    inverse_mellin_transform, laplace_transform, inverse_laplace_transform,
    fourier_transform, inverse_fourier_transform,
    sine_transform, inverse_sine_transform,
    cosine_transform, inverse_cosine_transform,
    a = symbols("a")
 
    assert hankel_transform(1/r, r, k, 0) == 1/k
    assert inverse_hankel_transform(1/k, k, r, 0) == 1/r
 
    assert hankel_transform(
        1/r**m, r, k, 0) == 2**(-m + 1)*k**(m - 2)*gamma(-m/2 + 1)/gamma(m/2)
        2**(-m + 1)*k**(m - 2)*gamma(-m/2 + 1)/gamma(m/2), k, r, 0) == r**(-m)
 
    assert hankel_transform(1/r**m, r, k, nu) == (
        2*2**(-m)*k**(m - 2)*gamma(-m/2 + nu/2 + 1)/gamma(m/2 + nu/2))
    assert inverse_hankel_transform(2**(-m + 1)*k**(
        m - 2)*gamma(-m/2 + nu/2 + 1)/gamma(m/2 + nu/2), k, r, nu) == r**(-m)
 
    assert hankel_transform(r**nu*exp(-a*r), r, k, nu) == \